Mechanical thrombectomy in patients with milder strokes and large vessel occlusions: a multicenter matched analysis - Nagel, Simon; Messer, Mirko; Ringleb, Peter A.; Möhlenbruch, Markus Alfred (Stroke, 2018)
Background and Purpose: We aimed to describe the safety and efficacy of immediate mechanical thrombectomy (MT) in patients with large vessel occlusions and low National Institutes of Health Stroke Scale (NIHSS) versus best medical management. Methods: Patients from prospectively collected databases of 6 international comprehensive stroke centers with large vessel occlusions (distal intracranial internal carotid, middle cerebral artery-M1 and M2 segments, or basilar artery with or without tandem occlusions) and NIHSS 0 to 5 were identified and divided into 2 groups for analysis: immediate MT or initial best medical management which included rescue MT after neurological deterioration (best medical management-MT). Uni- and multivariate analyses and patient-level matching for age, baseline NIHSS, and occlusion site were performed to compare baseline and outcome variables across the 2 groups. The primary outcome was defined as good outcome (modified Rankin Scale score, 0-2) at day 90. Safety outcome was symptomatic intracranial hemorrhage as defined by the ECASS (European Cooperative Acute Stroke Study) II and mortality at day 90. Results: Compared with best medical management-MT (n=220), patients with immediate MT (n=80) were younger (65.3±13.5 versus 69.5±14.1; P=0.021), had more often atrial fibrillation (44.8% versus 28.2%; P=0.012), higher baseline NIHSS (4, 0-5 versus 3, 0-5; P=0.005), higher Alberta Stroke Program Early CT Score (10, 7-10 versus 10, 5-10; P=0.023), more middle cerebral artery-M1, and less middle cerebral artery-M2 (41.3% versus 21.9% and 28.8% versus 49.3%; P=0.016) occlusions. The adjusted odds ratio for good outcome was 3.1 (95% CI, 1.4-6.9) favoring immediate MT. In the matched analysis, there was a 14.4% absolute difference in good outcome (84.4% versus 70.1%; P=0.03) at day 90 favoring immediate MT. There were no safety concerns. Conclusions: Our retrospective, pilot analysis suggests that immediate thrombectomy in large vessel occlusions patients with low NIHSS on presentation may be safe and has the potential to result in improved outcomes. Randomized clinical trials are warranted to establish the optimal management for this patient population.